A case report of esophageal tuberculosis (2014)
We report the case of an immune-competent man with symptoms of upper gastrointestinal bleeding secondary to esophageal ulcers of tubercular origin. Gastrointestinal involvement from Mycobacterium tuberculosis is rare even in patients with numerous occurrences of pulmonary and extrapulmonary diseases. The most frequently affected sites are the terminal ileum and the peritoneum. Esophageal tuberculosis is exotic and is usually secondary to extension from neighboring infected organs such as the mediastinal nodes and/or the bronchi. Clinical, endoscopic and radiological pictures of the esophageal disease often mimic malignancy. Tuberculosis treatment is the mainstay of treatment, and surgery is rarely required. © 2014 Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.